She wouldn't change a thing - Adlakha, Sarah (Forge, 2021)
"Sliding Doors meets Life After Life in Sarah Adlakha's story about a wife and mother who is given the chance to start over at the risk of losing everything she loves. A second chance is the last thing she wants. When thirty-nine year old Maria Forssmann wakes up in her seventeen-year-old body, she doesn't know how she got there. All she does know is she has to get back: to her home in Bienville, Mississippi, to her job as a successful psychiatrist and, most importantly, to her husband, daughters, and unborn son. But she also knows that, in only a few weeks, a devastating tragedy will strike her husband, a tragedy that will lead to their meeting each other. Can she change time and still keep what it's given her? Exploring the responsibilities love lays on us, the complicated burdens of motherhood, and the rippling impact of our choices, She Wouldn't Change a Thing is a dazzling debut from a bright new voice"--